Optimasi Pembentukan Bioflok Dari Chaetoceros sp., Thalassiosira sp. dan Bakteri Probiotik Melalui Variasi Salinitas Secara In Vitro - Nurdin, Suciati (bionature, 2017)
Abstract. Biofloc is a suspension contained in water consisting of microalgae, and bacteria that are potentially developed in the field of aquaculture that is as a natural food because of high protein content as well as alternative solutions to the problem of cultivation waste. This study aims to find out how the optimization of biofloc formation from Chaetoceros sp., Thalassiosira sp. and probiotic bacteria through the optimum salinity level used on the walne medium. This research was conducted at the Laboratory of Biology, State University of Makassar. This study was an experimental study using a completely randomized design (CRD) consisting of 5 treatments and 3 replications, namely with salinity 30 ppt (S1), treatment with salinity 25 ppt (S2), treatment with salinity 20 ppt (S3), treatment with salinity 15 ppt (S4), and 5 ppt (S5) salinity treatment on walne medium with using a combination of inoculants Chaetoceros sp., Thalassiosira sp. and probiotic bacteria. Parameters observed were biomass (dry weight) floc, floc volume, floc activity, temperature, pH, light intensity, and aeration rate. Data were analyzed using Analysis of Variance (ANOVA) followed by Duncan test (α 0.05). The result of the research shows that the salinity of 25 ppt is the optimum salinity for biofloc formation which is indicated by the highest floc biomass, the highest floc volume, and the highest floc activity with floc biomass indicator 0.00546 g / ml, floc volume 0.0071 ml, and floc activity 77.0262%.            Keywords: Biofloc, Salinity, Chaetoceros sp., Thalassiosira sp., Probiotic Bacteria